Berberine-based self-assembly agents with enhanced synergistic antitumor efficacy - Wang, Yun; Li, Zhongrui; Zhang, Haili; Wu, Peiye; Zhao, Yu; Li, Renshi; Han, Chao; Wang, Lei (Frontiers in Pharmacology, 2024)
Tumors are still a major threat to people worldwide. Nanodrug delivery and targeting systems can significantly improve the therapeutic efficacy of chemotherapeutic drugs for antitumor purposes. However, many nanocarriers are likely to exhibit drawbacks such as a complex preparation process, limited drug-loading capacity, untargeted drug release, and toxicity associated with nanocarriers. Therefore, new therapeutic alternatives are urgently needed to develop antitumor drugs. Natural products with abundant scaffold diversity and structural complexity, which are derived from medicinal plants, are important sources of new antitumor drugs. Here, two carrierfree berberine (BBR)-based nanoparticles (NPs) were established to increase the synergistic efficacy of tumor treatment. BBR can interact with glycyrrhetinic acid (GA) and artesunate (ART) to self-assemble BBR-GA and BBR-ART NPs without any nanocarriers, respectively, the formation of which is dominated by electrostatic and hydrophobic interactions. Moreover, BBR-GA NPs could lead to mitochondriamediated cell apoptosis by regulating mitochondrial fission and dysfunction, while BBR-ART NPs induced ferroptosis in tumor cells. BBR-based NPs have been demonstrated to possess significant tumor targeting and enhanced antitumor properties compared with those of simple monomer mixes both in vitro and in vivo. These carrierfree self-assemblies based on natural products provide a strategy for synergistic drug delivery and thus offer broad prospects for developing enhanced antitumor drugs.